Disparitas Pemidanaan dalam Tindak Pidana Korupsi yang Mengakibatkan Kerugian Keuangan Negara - Jaya, Muhammad Indra; Karim, M. Said; Muchtar, Syamsuddin (Al-Mizan (e-Journal), 2024)
This study aims to analyze legal factors and factors of law enforcement officials that influence the disparity in sentencing for corruption which results in state losses. The type of research used is empirical normative legal research. The results of the study show that (1) the legal factor in the presence of disparity decisions regarding corruption crimes has not been optimal because the minimum criminal sanctions in the corruption law cause disparity in sentencing which is quite disturbing due to the non-uniformity in the provision of minimum sentences for similar offenses. (2) the factor of law enforcement officials as the cause of the disparity in sentencing of corruption case decisions is very clearly seen and felt to be very unfair to each other, there is no clear guideline regarding the prevention of disparity in corruption criminal rulings so law enforcement officers exercise their power to decide similar offenses the pretext of the judicial power law.